Penggunaan Media Quizizz dalam Meningkatkan Keaktifan Belajar Siswa pada Pembelajaran PAI dan BP di Kelas VIII SMP Negeri 1 Jenangan Ponorogo - Septya Azhari Putri Wardana; Zamzam Mustofa (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Islamic Religious Education and Character Education learning has an important role in shaping students' character and morals. However, the low level of student learning activity is still a challenge in the learning process. This is caused by the use of conventional learning methods that are less interesting and interactive, so that students tend to be passive. As an alternative, digital media such as Quizizz media offers a more innovative and enjoyable learning approach to increase student active participation. This study aims to describe how the use of Quizizz media can (1) increase student learning activity in group discussions, (2) increase learning activity in daring to ask questions, and (3) increase student participation in answering questions in Islamic religious education learning in class VIII of SMP Negeri 1 Jenangan Ponorogo. The research method used is descriptive qualitative with interview, observation, and documentation techniques. Data were analyzed using the Milles and Huberman techniques, namely data collection, reduction, presentation, and drawing conclusions. The results of the study show that the use of Quizizz media (1) increases student activity in group discussions with an interactive and fun atmosphere, (2) encourages students to be more confident in asking questions with direct feedback that helps them understand the material, (3) can increase students' responses in answering questions, train focus, speed of thinking and understanding through a scoring system and time limits.